2018
DOI: 10.1089/dna.2017.4012
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA EBF3-AS Promotes Neuron Apoptosis in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia; its pathophysiological mechanism remains unclear. Long noncoding RNAs (lncRNAs) play key roles in AD. lncRNA EBF3-AS has been found dysregulated in AD, which is abundantly expressed in the brain. The aim of this study was to investigate the role of EBF3-AS in AD. Results showed that the expressions of lncRNA EBF3-AS and EBF3 (early B cell factor 3) were upregulated in hippocampus of APP/PS1 mice (AD model mice). EBF3-AS knockdown by siRNA inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…Zhao et al disclosed that lncRNA NEAT1 promoted the progression of AD by modulating the miR-124/BACE1 axis [23]. Also, reduced lncRNA EBF3-AS expression could overturn Aβ-induced apoptosis of SH-SY5Y cells [24]. In the present study, Aβ could enhance p-Tau protein level, repressed viability and promoted apoptosis of SH-SY5Y and SK-N-SH cells.…”
Section: Discussionsupporting
confidence: 54%
“…Zhao et al disclosed that lncRNA NEAT1 promoted the progression of AD by modulating the miR-124/BACE1 axis [23]. Also, reduced lncRNA EBF3-AS expression could overturn Aβ-induced apoptosis of SH-SY5Y cells [24]. In the present study, Aβ could enhance p-Tau protein level, repressed viability and promoted apoptosis of SH-SY5Y and SK-N-SH cells.…”
Section: Discussionsupporting
confidence: 54%
“…Antisense transcript of EBF3 (EBF3-AS) reduces early B cell factor 3 (EBF3) mRNA expression and promotes cell death. In an AD mouse model and Aβ-treated cells, EBF3-AS upregulation was found to promote apoptosis [97,103]. NAT-RAd18 is an antisense transcript of RAd18.…”
Section: Ncrnas In the Regulation Of Ad-associated Apoptosismentioning
confidence: 99%
“…BC1, another type of lncRNA, is found to induce APP mRNA translation via association with fragile X syndrome protein (FMRP) in mouse model AD brains ( Zhang T. et al, 2017 ). It was recently reported that EBF3 knockdown can reverse Aβ25-35-induced apoptosis in SH-SY5Y cells, and that lncRNA EBF3-AS promotes neuron apoptosis in AD through regulation of EBF3 expression ( Gu et al, 2018 ). Furthermore, the overexpression of Aβ and Aβ-42 in AD could increase BACE1 antisense transcript lncRNA levels, leading to amyloid protein aggregation ( Faghihi et al, 2008 ).…”
Section: Long Non-coding Rnas In Admentioning
confidence: 99%